GROSSRAUM C21: Experiencing intangible fields of sovereignty, expansionism and imposition of state-of-emergency regimes - Yannis Karpouzis; Karailias, Yorgos; Yorgos Prinos; Pavlos Fysakis (Design/Arts/Culture, 2024)
This project is a collective site-specific exhibition that took place as a parallel action to the Documenta 14 happenings in Athens. Despite being showcased as a progressive decision by the Documenta institution to move the exhibitions for the first time out of Germany into another country—and perhaps to indicate with this gesture its solidarity with Greece—for many Greek intellectuals and artists this narrative seemed equally colonial and imperialistic. A sticker in the city center summarized the critical approach toward the art institution: “Dear Documenta, I refuse to exoticize myself to increase your cultural capital. Sincerely, the people.” Thus, a few anti-Documenta performances and art happenings were organized during April and May 2017, one of them being "Grossraum 21C"